The artistic representation of the idea of true Christianity in the Korelenko’s short-story «The Old Bell-Ringer» - Silina, L.A. (Âzyk i tekst, 2016)
The article deals with the problem of the Christian understanding of life and death in the works of VG Korolenko. The main features of the Christian worldview are analyzed, which have found artistic expression in the image of the main character of the story. В статье рассматривается проблема христианского осмысления жизни и смерти в творчестве В.Г. Короленко. Анализируются основные черты христианского мировидения, нашедшие художественное воплощение в образе главного героя произведения.